Learn Qt 5 : Build modern, responsive cross-platform desktop applications with Qt, C++, and QML. - Sherriff, Nicholas (Packt Publishing, 2018)
Qt is a mature and powerful framework for delivering sophisticated applications across a multitude of platforms. It has a rich history in the Linux world, is widely used in embedded devices and has made great strides in the Mobile arena over the past few years. However, in the Microsoft Windows and Apple Mac OS X worlds, the dominance of ...